Escherichia coli Can Adapt Its Protein Translocation Machinery for Enhanced Periplasmic Recombinant Protein Production - Karyolaimos, Alexandros; Dolata, Katarzyna Magdalena; Antelo-Varela, Minia; Mestre Borras, Anna; Elfageih, Rageia; Sievers, Susanne; Becher, Dörte; Riedel, Katharina; de Gier, Jan-Willem (Frontiers in Bioengineering and Biotechnology, 2020)
Recently, we engineered a tunable rhamnose promoter-based setup for the production of recombinant proteins in E. coli. This setup enabled us to show that being able to precisely set the production rate of a secretory recombinant protein is critical to enhance protein production yields in the periplasm. It is assumed that precisely setting the production rate of a secretory recombinant protein is required to harmonize its production rate with the protein translocation capacity of the cell. Here, using proteome analysis we show that enhancing periplasmic production of human Growth Hormone (hGH) using the tunable rhamnose promoter-based setup is accompanied by increased accumulation levels of at least three key players in protein translocation; the peripheral motor of the Sec-translocon SecA, leader peptidase (LepB) and the cytoplasmic membrane protein integrase/chaperone YidC. Thus, enhancing periplasmic hGH production leads to increased Sec-translocon capacity, increased capacity to cleave signal peptides from secretory proteins and an increased capacity of an alternative membrane protein biogenesis pathway, which frees up Sec-translocon capacity for protein secretion. When cells with enhanced periplasmic hGH production yields were harvested and subsequently cultured in the absence of inducer, SecA, LepB and YidC levels went down again. This indicates that when using the tunable rhamnose-promoter system to enhance the production of a protein in the periplasm, E. coli can adapt its protein translocation machinery for enhanced recombinant protein production in the periplasm.